2018
DOI: 10.1186/s12944-018-0798-1
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral-blood gene expression profiling studies for coronary artery disease and its severity in Xinjiang population in China

Abstract: BackgroundAlterations in gene expression in peripheral blood cells play a curtail role in the presence and extent of coronary artery disease (CAD), but its severity reflected by gene expression alterations in peripheral blood cells is still unknown in Xinjiang population in China.MethodsGlobal gene expression profiling in peripheral blood was used to explore differentially expressed genes in coronary artery stenosis patients. RNA was extracted from peripheral blood of 9 controls without coronary stenosis and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Previous studies have shown the gene expression of peripheral blood monocytes may be involved in the formation and development of atherosclerosis and CAD. But most studies concentrate on patients in normal and stenosis coronary artery ( Sinnaeve et al, 2009 ; Liu et al, 2018 ), or patients with acute myocardial infarction and stable CAD ( Kiliszek et al, 2012 ; Holvoet et al, 2019 ), which demonstrate little evidence of gradual progression of CAD. In this study, we analyze and compare the gene expression of peripheral blood monocytes in normal coronary artery, intermediate lesion, and myocardial infarction patients with high-throughput sequencing technique.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the gene expression of peripheral blood monocytes may be involved in the formation and development of atherosclerosis and CAD. But most studies concentrate on patients in normal and stenosis coronary artery ( Sinnaeve et al, 2009 ; Liu et al, 2018 ), or patients with acute myocardial infarction and stable CAD ( Kiliszek et al, 2012 ; Holvoet et al, 2019 ), which demonstrate little evidence of gradual progression of CAD. In this study, we analyze and compare the gene expression of peripheral blood monocytes in normal coronary artery, intermediate lesion, and myocardial infarction patients with high-throughput sequencing technique.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that hyperglycemic condition could activate NF-κβ1, which could trigger several transcriptions of a vast array of genes encoding proinflammatory cytokines such as IL1B, IL6, and IL12Bwas associated in the pathogenesis of atherosclerosis and consequently contributed to modulating the susceptibility to CHD [58][59][60]. Moreover, it was demonstrated that MAPK14 had a proinflammatory gene that was significantly up-regulated in type 2 diabetes mellitus and CHD [61][62][63]. The current study results have shown that the mRNA level of NF-κβ1, IL6, IL12B, and MAPK14 were up-regulated in patients with T2D alone and T2D plus CHD.…”
Section: Discussionmentioning
confidence: 99%
“…Activated immunity also may be the common antecedent of both T2D and CHD, which probably developed in patients with diabetes and, consequently, coronary atherosclerosis. Furthermore, it was demonstrated in the study by Liu et al that the toll-like receptor signaling pathway interfered in the development of coronary artery stenosis and was associated with CHD severity [62]. Finally, to validate results, a single gene expression analysis of five randomly selected genes was conducted via Q-RT-PCR with increased and different sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous bioinformatic studies had extensively analyzed a vast amount of microarray data involving CAD from online databases to laboratory experiments. Their results showed that many peripheral immune genes of CAD patients had significant changes compared with the control groups, including but not limited to CXCL8, TNF, SOCS3, TNFAIP3, CD86, C1QB, CD53, C1QC, NCF2, ITGAM, MAPK1, MAPK3, MAPK13, MAPK14, JUN, CHUK, PIK3CB, TLR4, IFNAR1, TLR2, MYD88, IRAK4, CSF3, IL-1A, CCR7 and IL-18 [7][8][9][10]. However, these projects' current sample scale and scope are still limited.…”
Section: Introductionmentioning
confidence: 99%